Contemporary treatment of a Class II division 1 case - Alam, MK (Bangladesh Journal of Medical Science, 2012)
A 17 year-old Bangladeshi female presented with a severe Class II division 1 incisor relationship on a mild Skeletal II base. Crowding was moderate in the upper arch. The lower arch was well aligned. Treatment was commenced using fixed appliances and followed by extractions of upper first premolars. This case illustrates the versatility of the fixed appliances in the treatment of those cases exhibiting Class II division 1 malocclusion with crowding. DOI: http://dx.doi.org/10.3329/bjms.v11i1.9827 BJMS 2012; 11(1): 63-65